EFEKTIVITAS VECTOBAC DAN PREDATOR MESOCYCLOPS ASPERICORNIS SEBAGAI JASAD PENGENDALI HAYATI JENTIK AEDES AEGYPTI DALAM GENTONG AIR - Ambar Yuniarti, Retno; Ch.P, Blondine (Lembaga Penelitian Universitas YARSI, 2005)
Dengue Haemorrhagic Fever (DHF) was one of the acute and infectious disease and was still a problem of public health in Indonesia. This was caused the spread of the Aedes aegypti mosquito in the country, except at the altitude of more than one thousand meters above sea level. The spread of DHF was connected with the breeding place of the DHF vector. The use of chemical insecticides for vector control has been conducted for some time. Frequent use of insecticides has caused resistence of the mosquito towords the insecticide. Nowdays, biological control agents was developed. The aim of the study is to know the effectivity of the VectoBac and Mesocyclops aspericornis predator both applied individually and combination for controling of Ae. aegypti larvae in the water jar. The study was conducted in January until August 2003 in a DHF endemic area at Kupang Rengas, Kupang Village, Ambarawa subdistrict, Semarang regency, Central Java. The design of the study was quasy experimental comparing before and after intervention using external difference groups. Purposive sampling was conducted. The ten sample size were used for each treatment. The result showed that VectoBac was effective to reduce the Ae. aegypti larvae density until the fifth week reaching a percentage of 79,31 ? 96,04%. M. aspericornis predator was effective to reduce the Ae. aegypti larvae density in the seventh week until the twelfth week was 70,69 ? 75,09%. The combination of VectoBac and M. aspericornis predator was effective to reduce Ae. aegypti larvae density until the twelfth week reaching a percentage of 96,56 ? 100%.